Pericardial tamponade during pembrolizumab treatment in a patient with advanced lung adenocarcinoma: A case report and review of the literature. Issue 5 (17th March 2020) - Harada, Kazuaki; Ogasawara, Makoto; Shido, Akane; Meno, Akimitsu; Oda, Soichiro; Yoshida, Shota; Yoshida, Sonoe; Yoshikawa, Ayumu; Ebata, Ko; Abiko, Satoshi; Kawagishi, Naoki; Sano, Itsuki; et al.
Abstract: Several studies have demonstrated increased pericardial effusion during anti‐PD‐1 immunotherapy, and treatment in patients who have developed pericardial tamponade is controversial. In this study, we describe a 63‐year‐old woman with stage IVA lung adenocarcinoma given pembrolizumab as a first‐line therapy. After four cycles of pembrolizumab treatment, the patient suddenly developed a pericardial tamponade. Although pericardial effusion was increased, her tumor lesions were reduced. After an emergency pericardiocentesis, she continued the pembrolizumab therapy without recurrent pericardial effusions for three months until the primary tumor and lymph node metastasis progressed. Nine months after the pericardiocentesis, the patient died of progressive lung cancer, but pericardial effusion did not recur throughout the treatment course. This case study suggests that pembrolizumab therapy can be continued with a strict follow‐up in some patients with pembrolizumab‐induced pericardial tamponade. Key points: Significant findings of the study Our patient developed pericardial tamponade during pembrolizumab treatment but continued pembrolizumab treatment after emergency pericardiocentesis without recurrent pericardial effusions. What this study adds Pembrolizumab treatments may be resumed with a strict follow‐up in some patients with treatment‐related pericardial tamponade.